Genomics of hypertension. (July 2017) - Padmanabhan, Sandosh; Aman, Alisha; Dominiczak, Anna F.
Abstract: A complex network of interacting pathways involving renal, neural, endocrine, vascular and other mechanisms controls the main determinants of blood pressure – cardiac output and total peripheral resistance. Multiple genes within each of these systems contribute to the specialized functions regulating blood pressure. The monogenic forms of blood pressure dysregulation have provided valuable insights into blood pressure regulation and expanded our understanding of both the mechanisms and the treatment of hypertension. Genome wide association studies have identified over 100 single nucleotide polymorphisms associated with blood pressure phenotypes and have identified plausible novel pathways of BP regulation and putative drug targets.